FRP composites for reinforced and prestressed concrete structures [ a guide to fundamentals and design for repair and retrofit - Balaguru, Perumalsamy N.; Giancaspro, James; Nanni, Antonio , 1951- (London : Taylor & Francis, 2009)
Deals with the fundamentals of composites, and basic design principles, and provides guidelines for design. This book focuses on the repair and retrofit of un-reinforced, reinforced and prestressed
1. Constituent materials -- 2. Fabrication techniques -- 3. Common repair systems -- 4. Flexure: reinforced concrete -- 5. Flexure: prestressed concrete -- 6. Shear in beams -- 7. Columns -- 8. Load testing
Description based on print version record
Includes bibliographical references and index
Keywords: Fiber-reinforced plastics; Prestressed concrete construction -- Maintenance and repair; Reinforced concrete construction -- Maintenance and repair